TRAUMA HEALING STRATEGIES THROUGH PAPPASANG KALINDAQDAQ MANDAR AS AN ECONOMIC RECOVERY EFFORT IN EARTHQUAKE-PRONE AREAS IN WEST SULAWESI - Putra Safa'at; Anriawan Anriawan; Asno Y. Tore; Putri Alicia Pratiwi; Hermaliya Jumita Sari; Abdul Galib (SEAN Institute, 2023)
West Sulawesi Province is an area with the highest disaster risk index in Indonesia in 2022. In the last decade, the most common disaster in West Sulawesi is the earthquake, which has traumatised the community and crippled the economy. This research will provide the right strategy in handling trauma in earthquake-prone areas in West Sulawesi which is expected to be able to restore the community's economy. This research is a qualitative research using a phenomenological approach. The phenomenological analysis used adheres to transedental phenomenology. Based on the results of the research conducted, it was found that one of the appropriate strategies in handling trauma is trauma healing through the local wisdom of Pappasang Kalindaqdaq Mandar which contains various messages and at the same time motivation that can treat trauma in post-earthquake communities to return to their activities so that they can restore the economy that was once paralysed.